Autistic phenomenology: past, present, and potential future - Green, Jonathan; Shaughnessy, Nicola (Frontiers in Psychology, 2023)
We are now at a transition point in autism conceptualisation, science, and clinical practise, where phenomenology could play a key role. This paper takes a broad view of the history of phenomenological perspectives on the autism concept and how this has evolved over time, including contemporaneous theory and methods. Early inquiry from a clinical perspective within the tradition of classical continental phenomenology, linked closely to the consideration of schizophrenia, is contrasted with emerging observations of child development and a period in the second half of the twentieth century of scientific inquiry into a behavioural autistic phenotype where there was little or no phenomenological aspect; a phenotype that has determined the recent scientific and clinical conceptualisation of autism within current nosology. We then mark a more recent reawakening of interdisciplinary interest in subjective experience and phenomenological inquiry, which itself coincides with the increasing prominence and salience of the neurodiversity movement, autistic advocacy, and critical autism studies. We review this emerging phenomenological work alongside a contemporaneous clinical phenomenology perspective and representations of autistic experience from within the extensive literature (including life writing) from autistic people themselves; all perspectives that we argue need now be brought into juxtaposition and dialogue as the field moves forward. We argue from this for a future which could build on such accounts at a greater scale, working toward a more co-constructed, systematic, representative, and empirical autistic phenomenology, which would include citizen and participatory science approaches. Success in this would not only mean that autistic experience and subjectivity would be re-integrated back into a shared understanding of the autism concept, but we also argue that there could be the eventual goal of an enhanced descriptive nosology, in which key subjective and phenomenological experiences, discriminating for autism, could be identified alongside current behavioural and developmental descriptors. Such progress could have major benefits, including increased mutual empathy and common language between professionals and the autistic community, the provision of crucial new foci for research through aspects of autistic experience previously neglected, and potential new supportive innovations for healthcare and education. We outline a programme and methodological considerations to this end.